Navigating Writing Challenges: A Study on High-Use Learning Strategies Among Successful EFL Learners in Indonesia - Rezky Fakhir Hilmi; Yenni Rozimela (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing in a foreign language presents challenges related to grammar, vocabulary, coherence, and self-regulation. This study investigates the writing learning strategies employed by successful EFL learners in the English Education Study Program at Universitas Negeri Padang. The objective is to identify the most frequently used strategies to overcome these difficulties. A quantitative descriptive approach was employed, utilizing a survey questionnaire to collect data from a purposive sample of 30 successful EFL learners. The questionnaire assessed the frequency of various writing strategies, categorized into metacognitive, cognitive, compensation, social, memory, and affective strategies. Findings indicate that all strategy types fall under the "High Use" category. Metacognitive strategies were the most frequently employed (mean = 4.1), emphasizing planning, monitoring, and evaluating writing. Compensation strategies (mean = 3.9) and cognitive strategies (mean = 3.7) were also widely used, suggesting active learner efforts to address language gaps. Social and memory strategies showed similar levels of application (mean = 3.6), highlighting the role of peer support and memory aids. Affective strategies, though slightly lower (mean = 3.5), remained within the high-use category for managing emotions. With an overall mean of 3.7, the results suggest that frequent and diverse strategy use significantly contributes to writing proficiency. The high reliance on metacognitive strategies underscores their importance in self-regulated learning. These findings offer insights for educators seeking to enhance EFL writing instruction through strategy-based approaches, particularly by fostering metacognitive awareness and self-regulation.